The Burstiness of Star Formation at z ∼ 6: A Huge Diversity in the Recent Star Formation Histories of Very UV-faint Galaxies - Ryan Endsley; John Chisholm; Daniel P. Stark; Michael W. Topping; Lily Whitler (The Astrophysical Journal)
IRAC data have long implied that early ( z  ≳ 6) galaxies often have very high specific star formation rates (sSFRs ≳ 30 Gyr ^−1 ), but JWST data have shown that at least some early galaxies are forming stars far less vigorously. Here, we systematically analyze the recent star formation histories (SFHs) of a large ( N = 368) sample of z  ∼ 6 Lyman-break galaxies (LBGs) spanning −22 ≲  M _UV  ≲ −16 assembled from Advanced Camera for Surveys+NIRCam imaging in the GOODS and A2744 fields. We find that very low H α -to-UV luminosity ratios ( L _H _α / L _UV ) and strong recent downturns in star formation rate (SFR) are ≈5× more common among the UV-faintest subset of our sample (〈 M _UV 〉 = −17.4) compared to the brightest subset (〈 M _UV 〉 = −20.0). The frequency of high L _H _α / L _UV and strong recent SFR upturns is approximately constant with UV luminosity. We discuss how bursty SFHs naturally reproduce this much greater diversity in recent SFHs among very UV-faint galaxies. Using public NIRSpec/prism data, we newly confirm recent strong SFR downturns among three LBGs in our sample, and validate our photometric inferences on key SFH signatures among z  ∼ 6 LBGs in general. Our results imply that early galaxies frequently cycle through phases of rapid stellar mass assembly and other periods of much slower growth. This yields huge (≳1–2 mag) fluctuations in M _UV on rapid (∼10–30 Myr) timescales, helping explain the surprising abundance of z  > 10 galaxies. Finally, we caution that this burstiness causes all existing high-redshift samples (particularly line-selected samples) to be far less complete to galaxies with long recent phases of low sSFR compared to those currently undergoing a burst.